Case report: Gemcitabine intravesical hyperthermic infusion combined with tislelizumab in muscle invasive bladder urothelium carcinoma - Du, Zheng; Yin, Huaqi; Zhao, Shiming; Ma, Yongkang; Sun, Zhenghui; Dong, Bingqi; Zhu, Mingkai; Zhu, Chaoshuai; Peng, Jiangshan; Yang, Tiejun (Frontiers in Oncology, 2022)
Background: Muscle invasive bladder urothelium carcinoma is a common urinary tract tumor. With the deepening of research, more and more treatment methods are applied in clinical practice, extending the life of patients. Among them, the clinical application of chemotherapeutic intravesical hyperthermia and tumor immunotherapy provides new ideas for our treatment. Case report: An 81-year-old female patient was diagnosed with stage T2N0M0 bladder cancer in our hospital. Because the patient and her family were keen to preserve her bladder, they declined surgery and opted for combined chemotherapy. After informed consent from the patient and her family, she received cisplatin combined with gemcitabine intravesical hyperthermic infusion. But the side effects of cisplatin made her intolerable to chemotherapy. With their informed consent we changed her to tislelizumab in combination with gemcitabine intravesical hyperthermic infusion to continue her treatment. During the subsequent follow-up visits, we found a surprising effect of the treatment. Conclusion: Gemcitabine intravesical hyperthermia therapy combined with tislelizumab in the treatment of muscle invasive bladder urothelium carcinoma may bring more benefits to the treatment of some patients who are inoperable or refuse surgery.